2017
DOI: 10.1007/s00787-017-1069-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictive validity of a service-setting-based measure to identify infancy mental health problems: a population-based cohort study

Abstract: Measures to identify infancy mental health problems are essential to guide interventions and reduce the risk of developmental psychopathology in early years. We investigated a new service-setting-based measure the Copenhagen Infant Mental Health Screening (CIMHS) within the general child health surveillance by community health nurses (CHN). The study population of 2973 infants was assessed by CIMHS at age 9-10 months. A subsample of 416 children was examined at age 1½ years, using parent interviews including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 69 publications
2
18
0
1
Order By: Relevance
“…The use of different tools to assess RPs before and after 6 months might have influenced the results, and potentially, reduced the effect sizes of the associations. However, it is considered a strength that the CHNs used a validated measure of feeding and eating, sleeping and excessive crying at child age 9–10 months28 32, which by large correspond to the questions in another measure of RPs, the Baby–DIPS (Diagnostic Interview for Regulatory Problems)interview 36…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of different tools to assess RPs before and after 6 months might have influenced the results, and potentially, reduced the effect sizes of the associations. However, it is considered a strength that the CHNs used a validated measure of feeding and eating, sleeping and excessive crying at child age 9–10 months28 32, which by large correspond to the questions in another measure of RPs, the Baby–DIPS (Diagnostic Interview for Regulatory Problems)interview 36…”
Section: Discussionmentioning
confidence: 99%
“…Feeding and eating, sleeping and excessive crying were evaluated as being within the normal range or not 29. At the home visit between 8 and 11 months, the CHNs used a validated tool, the Copenhagen Infant Mental Health Questionnaire,31 which includes specified variables on feeding and eating, on sleeping and on excessive crying, all answered by yes/no to the presence of any problem or not 28 32. The parent–child relationship was evaluated from the parents’ description of their expectations to and their handling of the child, and the CHN’s observations of the interaction and emotional attunement between parents and child, and the relation was finally recorded by the CHNs as problematic or not.…”
Section: Methodsmentioning
confidence: 99%
“…Two widespread screening methods are the Alarm Baby Distress Scale (ADBB) [17] and the Copenhagen Infant Mental Health Screening [18]. Both screening methods have demonstrated high reliability and validity [1921]. A study has demonstrated that the Alarm Baby Distress Scale are well received by the health visitors and support their detection of problematic parent–infant relations and stimulate their communication with the parents about ways to stimulate relations and wellbeing [22].…”
Section: Discussionmentioning
confidence: 99%
“…Research has stressed, however, that many parents struggle to identify the optimal approach for transitioning from milk feeds to solid foods, particularly first-time parents (Harrison, Brodribb, & Hepworth, 2017). According to existing research, 25-35% of new parents in Western societies experience eating-related problems in relation to the introduction of solid foods (Ammitzbøll, Thygesen, Holstein, Andersen, & Skovgaard, 2018;Bryant-Waugh, Markham, Kreipe, & Walsh, 2010). Early problems may affect the parents negatively and cause frustration and, potentially, also an increased tendency towards depression (Lucarelli, 2013;Rask, Ørnbøl, Olsen, Fink, & Skovgaard, 2013).…”
Section: Introductionmentioning
confidence: 99%